2019
DOI: 10.1002/pd.5590
|View full text |Cite
|
Sign up to set email alerts
|

Is there still a role for nuchal translucency measurement in the changing paradigm of first trimester screening?

Abstract: Objectives:To give an overview of the genetic and structural abnormalities occurring in fetuses with nuchal translucency (NT) measurement exceeding the 95th percentile at first-trimester screening and to investigate which of these abnormalities would be missed if cell-free fetal DNA (cfDNA) were used as a first-tier screening test for chromosomal abnormalities.Methods: This is a national study including 1901 pregnancies with NT≥95th percentile referred to seven university hospitals in the Netherlands between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 40 publications
8
71
0
1
Order By: Relevance
“…To be able to compare the current data with the literature cohort tested with karyotyping, we took only microscopically visible aberrations into account. Strong association between chromosomal aberrations and fetal NT >3 mm was already suggested by Pandya et al 29 When karyotypically visible aberrations are taken into account, our pooled cohort showed 11% of abnormal cases, whereas the clinical data of Kagan et al 7 showed chromosomal aberrations in 7.1% of fetuses (p95 ‐> 3.4 mm, 507/7109), Äyräs et al 30 in 9.6% (p95 ‐> 3.4 mm, 65/679), Nicolaides et al 31 in 13% (NT = 3 mm 7/52) and Bardi et al 32 in 14% (p95‐p99, 124/894). Although the incidence of chromosome aberrations presented in this paper is within the previously published range (7%‐14%), one has to be aware that the incidence based on fetal invasive testing, such as in our study, might represent the upper bound risk estimate, but on the other hand, in population‐based studies the bias could be caused by missing pediatric cases with less pronounced symptoms caused by a chromosomal aberration that is not always evident at birth or even within the first 3 years.…”
Section: Discussionmentioning
confidence: 53%
“…To be able to compare the current data with the literature cohort tested with karyotyping, we took only microscopically visible aberrations into account. Strong association between chromosomal aberrations and fetal NT >3 mm was already suggested by Pandya et al 29 When karyotypically visible aberrations are taken into account, our pooled cohort showed 11% of abnormal cases, whereas the clinical data of Kagan et al 7 showed chromosomal aberrations in 7.1% of fetuses (p95 ‐> 3.4 mm, 507/7109), Äyräs et al 30 in 9.6% (p95 ‐> 3.4 mm, 65/679), Nicolaides et al 31 in 13% (NT = 3 mm 7/52) and Bardi et al 32 in 14% (p95‐p99, 124/894). Although the incidence of chromosome aberrations presented in this paper is within the previously published range (7%‐14%), one has to be aware that the incidence based on fetal invasive testing, such as in our study, might represent the upper bound risk estimate, but on the other hand, in population‐based studies the bias could be caused by missing pediatric cases with less pronounced symptoms caused by a chromosomal aberration that is not always evident at birth or even within the first 3 years.…”
Section: Discussionmentioning
confidence: 53%
“…The possibility of a differential diagnosis, such as Noonan syndrome, is only introduced when there are structural abnormalities, and PND has shown the NIPT result to be a false positive. This occurred in only two (1%) of our cases and further highlights the importance of 11‐ to 14‐week ultrasound which may indicate other chromosomal or congenital abnormalities not assessed by NIPT 34 …”
Section: Discussionmentioning
confidence: 55%
“…Implementation of two ultrasound scans in the first trimester if NIPT is performed early has to be discussed. Offering NIPT at 11+0-13+6 weeks in order to look for increased nuchal translucency and structural fetal anomalies, following the ISUOG guidelines, seems to be the more comprehensive approach [ 12 , 13 , 14 ]. A recent study showed that management would be changed in almost 10% of cases, when ultrasound was done before blood for NIPT was drawn [ 15 ].…”
Section: Introduction and Overviewmentioning
confidence: 99%